Analysis Of The Application Of The Nutmeg Agribusiness System In Hutumuri Country,South Leitimur District, Ambon City - Mariana Setitit; Ester Kembauw; Marvin Lawalata (Cita konsultindo, 2023)
This study aims to identify the nutmeg agribusiness system (Myristica fragrans) in Hutumuri Country, South Leitimur District, Ambon City. The determination of the number of research samples using the Slovin formula with the number of research samples was 61 nutmeg farmers. Data collection in this study was carried out through interviews and observations at the research site. The research method used is the descriptive method. Data analysis is carried out qualitatively. The results showed that the implementation of the nutmeg agribusiness system in Hutumuri Country has not run well. This is due to several factors, namely; 1) There is no full readiness of farmers in applying modern agricultural techniques, such as prioritizing the planting of superior seeds, the use of medicines and the use of agricultural equipment that can increase nutmeg production, except the availability of production machinery for advanced products, 2) Still using traditional cultivation practices.